2015
DOI: 10.1007/s11060-015-1766-5
|View full text |Cite|
|
Sign up to set email alerts
|

Survival prediction in high-grade gliomas using CT perfusion imaging

Abstract: Patients with high-grade gliomas usually have heterogeneous response to surgery and chemoirradiation. The objectives of this study were (1) to evaluate serial changes in tumor volume and perfusion imaging parameters and (2) to determine the value of these data in predicting overall survival (OS). Twenty-nine patients with World Health Organization grades III and IV gliomas underwent magnetic resonance (MR) and computed tomography (CT) perfusion examinations before surgery, and 1, 3, 6, 9, and 12 months after r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Yeung et al showed that patients with shorter OS had higher BV and PS in both regions than patients with longer OS (Fig. 6), and that post-radiotherapy BV in the peritumoral edema region could predict 24 months OS with sensitivities and specificities >80% [46]. Similar results have been demonstrated in DSC-MR studies [47,48].…”
Section: Prediction Of Prognosissupporting
confidence: 65%
“…Yeung et al showed that patients with shorter OS had higher BV and PS in both regions than patients with longer OS (Fig. 6), and that post-radiotherapy BV in the peritumoral edema region could predict 24 months OS with sensitivities and specificities >80% [46]. Similar results have been demonstrated in DSC-MR studies [47,48].…”
Section: Prediction Of Prognosissupporting
confidence: 65%
“…The CT perfusion imaging was performed on a clinical CT scanner (Discovery 750 HD, GE Healthcare, Waukesha, WI) according to previous work [ 16 ]. A two-phase CT perfusion scan, guided by a prior non-contrast CT scan that identified sixteen 1.25 mm thick sections to cover the entire brain, was performed for each animal.…”
Section: Methodsmentioning
confidence: 99%
“…The changes in CT numbers as a function of time can be measured using the dynamic series of CT perfusion images. After glioma cells implantation, baseline images were obtained on an average of 11 days (7–16 days) when the diameter of the tumor reached 4 mm [ 16 ]. Stereotactic radiosurgery (SRS) is an effective technique that delivers one or a few high dose (8–30 Gy) radiation per fraction [ 18 , 19 ] Rats were randomly assigned to control ( N = 18), acute response to SRS (Group SRS1, N = 6), and serial imaging after SRS (Group SRS2, N = 13) groups.…”
Section: Methodsmentioning
confidence: 99%
“…Published data have suggested that perfusion CT might be comparable to MRI [ 33 , 34 ]. Moreover, perfusion CT has been used to evaluate possible clinical benefits of pharmacology therapy in early stroke onset [ 35 ], as well as to predict survival in in high-grade gliomas [ 36 ].…”
Section: Computed Tomography (Ct)mentioning
confidence: 99%